Implementation of Disaster Risk Reduction and Management in a Philippine Public Elementary School - Bongayon, Michelle; Gervacio, Mydee; Padilla, Mary Grace; Ventura, Aries (Journal of Interdisciplinary Perspectives, 2025)
This study aimed to determine the status of the implementation of disaster risk reduction and management (DRRM) in a mega public school. Specifically, the respondents were 58 teachers from Cauayan South Central School, Cauayan City, Isabela. The respondents' profiles included sex, position, highest educational attainment, and the number of relevant trainings attended. The structured questionnaire used was modified and adapted from the Department of Education's School Disaster Risk Reduction and Management Manual. The results revealed that DRRM coordination and information management protocols were "well-implemented" as evinced by (M = 3.437). The activities in school disaster management were also rated as "well-implemented" (M = 3.339), while key indicators of education facilities (M = 3.147), learning environments (M = 3.190), and risk reduction and resilience education (M = 3.207) were rated as "implemented." The study found no significant differences in DRRM implementation based on sex (p = 0.064), position (p = 0.061), or highest educational attainment (p = 0.065). However, the number of relevant training sessions attended showed a significant difference (p = 0.001), with higher training attendance correlating with better DRRM implementation. Additionally, the study identified that some of the key challenges, according to the respondents, are shortages or lack of material resources (M = 3.138) and insufficient training programs (M = 3.034) being conducted at the school level. The study concluded that while DRRM measures are generally implemented, there should be targeted training and resource allocation to further improvements.